A Trade and Climate Agenda for Promoting CO2 Management through Carbon Markets - Espa, Ilaria (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
This paper discusses the importance of carbon capture and storage (CCS) technologies in achieving the Paris Agreement’s climate goals. The document highlights possible pathways for the integration of CCS into emission trading systems (ETS) to incentivize CCS deployment. The document identifies Carbon Contracts for Difference (CCfDs) as a promising support tool to bridge the cost gap for CCS by stabilizing revenues through government contracts based on carbon prices and looks into ways to implement a Carbon Storage Obligation (CSO), which would require entities to sequester a percentage of embedded carbon, creating demand for carbon storage units (CSUs) to finance storage infrastructure. The document also offers some insights on how these instruments may comply with or come into conflict with WTO rules. In short, this study emphasizes the need to design ETS-CCS integration policies that support investment while ensuring WTO compatibility.